Diagnosis of the Linking Activities of the Faculty of Agricultural Engineering of the Universidad TÃ©cnica de ManabÃ - Vera, Teresa Viviana Moreira; Vivas, Fe Esperanza Vivas; Triana, Sonia MarÃƒÂa Fleitas; Mero, Tanya Beatriz Bravo (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2017)
The aim of the study is to determine the contribution of universities to the development of society through linkage projects carried out by students of the Faculty of Agricultural Engineering at the Universidad TÃ©cnica de ManabÃ...